2017
DOI: 10.1111/aor.12887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orthostatism and Hemodialysis on Mean Heart Period and Fractal Heart Rate Properties of Chronic Renal Failure Patients

Abstract: The aim of this work was to evaluate the short-term fractal index (α ) of heart rate variability (HRV) in chronic renal failure (CRF) patients by identifying the effects of orthostatism and hemodialysis (HD), and by evaluating the correlation between α and the mean RR interval from sinus beats (meanNN). HRV time series were derived from ECG data of 19 CRF patients and 20 age-matched healthy subjects obtained at supine and orthostatic positions (lasting 5 min each). Data from CRF patients were collected before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
(65 reference statements)
1
8
0
9
Order By: Relevance
“…Yet, both allowed us to identify that the dynamic behavior of heart rate fluctuations in these patients is also modified. NAV subjects showed larger anti-correlated behavior at supine position (see α 1sign in Table 4 ) and only for these people did we find significant increments in both α 1 and α 1sign (i.e., larger regularity and less anti-correlation) as would be expected by the active standing maneuver [ 24 , 25 ]. An anti-correlated behavior of heart rate fluctuations can be attributed to a condition in which a modulating factor (e.g., the parasympathetic activity) exerts a dominant effect, whereas less anti-correlation is manifested when various regulatory factors participate [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Yet, both allowed us to identify that the dynamic behavior of heart rate fluctuations in these patients is also modified. NAV subjects showed larger anti-correlated behavior at supine position (see α 1sign in Table 4 ) and only for these people did we find significant increments in both α 1 and α 1sign (i.e., larger regularity and less anti-correlation) as would be expected by the active standing maneuver [ 24 , 25 ]. An anti-correlated behavior of heart rate fluctuations can be attributed to a condition in which a modulating factor (e.g., the parasympathetic activity) exerts a dominant effect, whereas less anti-correlation is manifested when various regulatory factors participate [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 88%
“…In response to the orthostatic stimulus, the vagal response decreases and the sympathetic one becomes more important, which is manifested by a HRV reduction showing a predominance of low-frequency over high-frequency oscillations [ 21 , 22 ]. This HRV reduction caused by the orthostatic challenge also introduces a distinctive dynamical change in such oscillations [ 23 , 24 , 25 ]. To characterize this behavior, the so-called scaling indices can be used [ 26 , 27 ], which quantify the fractal-like HRV irregularity along different time scales.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the short-term fractal index (α1) has a significant correlation with the mean heart rate in healthy people [ 24 , 25 ]. Although such correlation is lost in ESRD patients before hemodialysis, it is recovered after hemodialysis and so considered as an indicator of cardiovascular adaptability [ 24 , 26 ] as well as a potential marker to differentiate between adaptive changes to achieve a precise demand response and long-term adjustments for facing pathophysiological alterations that, in other physiological contexts, could be deleterious. During an orthostatic challenge, the change from a supine to standing up position modifies some RQA indices [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, whilst active standing was associated with increase in normalized LF and decrease in normalized HF during HD treatment, this was not the case when treatment with hemofiltration was used. Echeverria et al (2017) showed an increase in LF/HF in response to postural provocations before and after HD treatment.…”
Section: Non-invasive Electrophysiology In Dialysis Patientsmentioning
confidence: 96%